Paradoks Regulasi dan Realitas: Kritik atas Implementasi Perlindungan Hukum bagi Anak Penyandang Disabilitas Korban Kekerasan Seksual di Indonesia - Annas, Gilang Kresnanda; Fatiha, Nilam Amalia (UIN Sunan Kalijaga Yogyakarta, 2025)
The ratification of Law Number 8 of 2016 concerning Persons with Disabilities also seems to be a breath of fresh air that brings fundamental changes through changes in society's perspective on people with disabilities. However, after that period, the government seems not to be accustomed to this equality so that it often forgets people with disabilities when making legal policies. The translation of lines and legal texts in a policy tends to forget the disability group. This results in people with disabilities having minimal accessibility to legal protection, for example victims of immoral crimes with disabilities. The legal substance in the Criminal Procedure Code has not been able to pay attention to the characteristics of people with disabilities who are positioned as victims, which automatically makes them viewed as subjects who are not legally competent. The phenomenon of discrimination against people with disabilities is certainly a crucial topic that must be addressed immediately. Instead of giving different treatment, the government should be able to provide various supporting services as evidence of equal rights for the community. Therefore, this scientific article will discuss legal protection for children with disabilities who are victims of sexual violence in Indonesia to find out how the implementation of protection for victims with disabilities and what rights need to be accommodated to provide legal protection for victims of immoral acts with disabilities. The research findings indicate that legal protection can be provided through the provision of restitution and compensation, counseling services, medical assistance, legal accompaniment, and the delivery of case-related information to the victim or their family. Abstrak Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas juga seolah-olah menjadi angin segar yang membawa perubahan fundamental melalui perubahan perspektif masyarakat tentang penyandang disabilitas. Namun setelah masa-masa tersebut, pemerintah kiranya belum terbiasa dengan penyetaraan tersebut sehingga masih sering melupakan penyandang disabilitas ketika proses pembuatan kebijakan hukum. Penerjemahan baris-baris dan teks hukum dalam sebuah kebijakan cenderung melupakan kelompok disabilitas. Hal tersebut mengakibatkan penyandang disabilitas memiliki aksesbilitas perlindungan hukum yang minim, contohnya korban tindak pidana asusila penyandang disabilitas. Substansi hukum dalam KUHAP belum mampu memperhatikan karakteristik penyandang disabilitas yang berposisi sebagai korban, yang secara otomatis membuat mereka dipandang sebagai subjek yang tidak cakap hukum. Fenomena pendiskriminasian terhadap penyandang difabel tentu menjadi topik krusial yang harus segera dibenahi. Alih-alih memberikan perlakuan yang berbeda, seharusnya pemerintah dapat memberikan berbagai layanan pendukung sebagai bukti pemerataan hak masyarakat. Maka dari itu, artikel ilmiah ini akan membahas mengenai perlindungan hukum terhadap anak penyandang disabilitas korban kekerasan seksual di indonesia untuk mengetahui bagaimana pelaksanaan perlindungan korban penyandang disabilitas dan hak-hak apa saja yang perlu diakomodir untuk memberikan perlindungan hukum bagi korban tindak asusila penyandang disabilitas. Hasil penelitian menunjukkan bahwa pemberian perlindungan hukum dapat dilakukan melalui pemberian restitusi dan kompensasi, pemberian konseling, pelayanan atau bantuan medis, pendampingan hukum, dan pemberian informasi perkembangan perkara yang dialami oleh korban atau keluarganya